Quasi-2d fluids of dipolar superballs in an external field. Issue 19 (21st May 2015) - Linse, Per
<x xml:space="preserve">Abstract</x> (Top) Dipolar superballs with dipole moment in 001, 011, and 111-direction and (bottom) structure in quasi-2d fluids with an external field in the horizontal direction. The degree of attraction between strings depends and the structures formed depends decisively on the direction of the dipole in the principal axis system of the superballs.